Application of Purified Lawsone as Natural Dye on Cotton and Silk Fabric. (15th April 2015) - Hasan, Md. Mahabub; Abu Nayem, Khandakar; Anwarul Azim, Abu Yousuf Mohammad; Ghosh, Nayon Chandra
Abstract : The color which is obtained from the leaves of Henna, that is, Lawsonia inermis L., is used frequently in hair coloring. It is the chemical lawsone that is responsible for the reddish brown color. Its content makes it a substantive dye for dyeing the textile materials. This work concerns with the extraction and purification of natural dyestuff from a plant Lawsonia inermis L. and dyeing of cotton and silk fabric in exhaust dyeing method. The dye portion is isolated from the total extract by column chromatography and is evaluated by dyeing cotton and silk under different dyeing conditions. The color strength and fastness properties of the dye are undertaken by changing mordant and techniques of mordanting. The changes of colors have been noticed by using different types of mordant. The dye exhaustion percentage, wash, rubbing, and light fastness results reveal that the extract of henna can be used for coloration of cotton and silk fabric.